Improving rates of overweight, obesity and extreme obesity in New Zealand 4‐year‐old children in 2010–2016. Issue 12 (22nd December 2017) - Shackleton, N.; Milne, B. J.; Audas, R.; Derraik, J. G. B.; Zhu, T.; Taylor, R. W.; Morton, S. M. B.; Glover, M.; Cutfield, W. S.; Taylor, B.
Summary: Background: Prevalence of childhood obesity is high in developed countries, and there is a growing concern regarding increasing socio‐economic disparities. Objectives: To assess trends in the prevalence of overweight, obesity and extreme obesity among New Zealand 4‐year olds, and whether these differ by socio‐economic and ethnic groupings. Methods: A national screening programme, the B4 School Check, collected height and weight data for 75–92% of New Zealand 4‐year‐old children ( n  = 317 298) between July 2010 and June 2016. Children at, or above, the 85th, 95th and 99.7th percentile for age and sex adjusted body mass index (according to World Health Organization standards) were classified as overweight, obese and extremely obese, respectively. Prevalence rates across 6 years (2010/11 to 2015/16) were examined by sex, across quintiles of socio‐economic deprivation, and by ethnicity. Results: The prevalence of overweight, obesity and extreme obesity decreased by 2.2 [95% CI, 1.8–2.5], 2.0 [1.8–2.2] and 0.6 [0.4–0.6] percentage points, respectively, between 2010/2011 and 2015/2016. The downward trends in overweight, obesity and extreme obesity in the population persisted after adjustment for sex, ethnicity, deprivation and urban/rural residence. Downward trends were also observed across sex, ethnicity and deprivation groups. Conclusions: The prevalence of obesity appears to be declining in 4‐year‐old children in New Zealand across all socio‐economic and ethnic groups.